Rancang Bangun Aplikasi Mobile Learning Matematika pada Materi Geometri (Dimensi Tiga) Berbasis Android di MA Islamiyah Darul Irfan Sawangan Depok - Ilyas, Irsyad Khalid; Med Irzal; Fariani Hermin Indiyah (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2023)
Mobile Learning is learning through mobile wireless technology that supports everyone to access information and learning materials from anywhere and anytime. Mobile Learning Based on the reason that learning can be done anywhere and anytime. Mobile Learning has a broad scope because it uses commercial cellular networks. In the process, the presentation of e-learning based on this Android mobile application can be more interactive. Information on learning materials and access to materials can be presented up-to-date and in real time. This thesis aims to design and build a mobile learning application for mathematics on android-based three-dimensional material to make it easier for teachers to deliver geometry learning materials about three dimensions and make it easier for students to understand three-dimensional learning materials. Mathematical mobile learning application on Android-based three-dimensional material which was developed using the spiral model software development life cycle method. This application is built using the CodeIgniter framework and the Java programming language. Users in this application open 2, namely teachers who can present material in the form of videos and provide exercises for students, students who can see video-based learning materials and exercises carried out by teachers as a refusal given by students in understanding the material presented by the teacher concerned.